2003
DOI: 10.1016/s1472-6483(10)62088-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of culture environment on embryo quality and gene expression – experience from animal studies

Abstract: Recent studies comparing bovine oocyte maturation, fertilization and embryo culture in vivo and in vitro have demonstrated that the origin of the oocyte is the main factor affecting blastocyst yield, while the post-fertilization culture environment is critical in determining blastocyst quality, measured in terms of cryotolerance and relative transcript abundance, irrespective of the origin of the oocyte. Production of embryos in vitro, particularly when using an extended period of in-vitro culture, may predisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 86 publications
2
71
0
3
Order By: Relevance
“…At the end of G1, cells are committed to division and lose the ability to respond to external factors. The nonacquisition of cytoplasmic competence during oocyte maturation may result in a longer G2 phase, which will result in a greater sensitivity to external factors and may explain the intense embryo blockage that occurs in this embryonic stage (Biase et al, 2009;Lonergan et al, 2003). Unlike the IVF 8-16C embryos, all the transcripts were downregulated in the PA group, suggesting a failure in the mechanism of EGA, at least in relation to the events related to cell cycle.…”
Section: Discussionmentioning
confidence: 98%
“…At the end of G1, cells are committed to division and lose the ability to respond to external factors. The nonacquisition of cytoplasmic competence during oocyte maturation may result in a longer G2 phase, which will result in a greater sensitivity to external factors and may explain the intense embryo blockage that occurs in this embryonic stage (Biase et al, 2009;Lonergan et al, 2003). Unlike the IVF 8-16C embryos, all the transcripts were downregulated in the PA group, suggesting a failure in the mechanism of EGA, at least in relation to the events related to cell cycle.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, mouse embryos cultured under suboptimal conditions demonstrated differences in birthweight (Banrezes et al, 2011), imprinting (Fernandez-Gonzalez et al, 2004Rivera et al, 2008) and gene expression (Ecker et al, 2004;Rinaudo and Schultz 2004;Giritharan et al, 2007). Errors in imprinting in domestic animals have been linked to culture conditions as well (Lonergan et al, 2003). Adverse effects of in vitro culture may also affect human development, with evidence that shorter culture times yield better longterm outcomes (Kallen et al, 2010;Kalra et al, 2012) and that culture media composition can affect birthweights (Dumoulin et al, 2010;Nelissen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors argue that blastocyst culture might negatively affect the quality of embryo. Experiences from animal studies have shown that post-fertilization culture environment had a profound effect on the relative abundance of gene transcripts within the embryo and culture under suboptimal conditions could lead to perturbations in the pattern of expression [31,32]. This question remains a matter of debate.…”
Section: Discussionmentioning
confidence: 99%